2021
DOI: 10.1186/s13046-021-02090-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: LNCAROD enhances hepatocellular carcinoma malignancy by activating glycolysis through induction of pyruvate kinase isoform PKM2

Abstract: Background Mounting evidence has suggested the essential role of long non-coding RNAs (lncRNAs) in a plethora of malignant tumors, including hepatocellular carcinoma. However, the underlyling mechanisms of lncRNAs remain unidentified in HCC. The present work was aimed to explore the regulatory functions and mechanisms of LncRNA LNCAROD in HCC progression and chemotherapeutic response. Methods The expression of LNCAROD in HCC tissues and cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“… 9 , 27 , 28 Jia et al reported that activation of glycolysis improves tumor malignancy and chemoresistance of hepatocellular carcinoma. 29 And the study of Lin et al found that POU2F1 directly bound to the ALDOA promoter and then decreased the sensitivity to oxaliplatin in colon cancer cells by enhancing glycolysis. 30 Furthermore, targeting metabolism reprogramming was an efficient method to overcome the chemoresistance of pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 27 , 28 Jia et al reported that activation of glycolysis improves tumor malignancy and chemoresistance of hepatocellular carcinoma. 29 And the study of Lin et al found that POU2F1 directly bound to the ALDOA promoter and then decreased the sensitivity to oxaliplatin in colon cancer cells by enhancing glycolysis. 30 Furthermore, targeting metabolism reprogramming was an efficient method to overcome the chemoresistance of pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that lncRNAs, functioning as a ceRNA by competitively binding to miRNAs, affect aerobic glycolysis and participate in cancer progression and treatment resistance. For example, Jia et al demonstrated that the lncRNA LNCAROD induced pyruvate kinase isoenzyme M2 (PKM2) upregulation via sponging miR-145–5p, increased aerobic glycolysis in hepatocellular carcinoma cells, and was eventually involved in tumor malignancy and chemoresistance ( Jia et al, 2021 ). Xu et al had reported that LINC01448 promoted cell proliferation, cell invasion, and glucose consumption by modulating the miR-505/HK2 pathway in PAAD ( Xu Z. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The two isoforms of PKM, PKM1 and PKM2, are produced by the splicing of PKM. The long non-coding RNA LNCAROD could induce the upregulation of PKM2, eventually increasing cancer cell aerobic glycolysis, which is related to poor prognosis in HCC ( 10 ). PGK1 is an important glycolysis-related enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…One cause of the “Warburg effect” is the overexpression of glycolysis-related enzymes ( 8 ). The expression of the glycolysis-related enzymes hexokinase 2 (HK2) ( 8 ), 6-phosphofructo-2-kinase/fructose 2,6-bisphosphatase 3 (PFKFB3) ( 9 ), pyruvate kinase M (PKM) ( 10 ), phosphoglycerate kinase 1 (PGK1) ( 11 ), and lactate dehydrogenase A (LDHA) ( 12 ) in HCC were evaluated using TCGA expression profile data. The correlation between ABAT and glycolysis-related enzymes was also determined.…”
Section: Methodsmentioning
confidence: 99%